(untitled) (Itinera, 2023)
This work focuses on a particular figure of the monster: the hermaphrodite who has been considered significant since ancient times. In Middle Ages, the hermaphrodites were executed because of their deformity. This attitude changed later on and they started to be condemned as perverts. During the XIX century, Teratology wanted to include them in a monsters’ classification but the scientists found this work very difficult because they were influenced by novelists who considered the hermaphrodite a perfection’s emblem. In this case, it’s important to underline that Balzac and Hugo wrote about “double” monsters. It means that Balzac talked about people who were both male and female, while Hugo talked about characters with both dark and sublime soul. Balzac in particular considered the androgyne perfect because he didn’t show significant differences. So, this essay wants to analyze the debates about hermaphrodite and its doubleness.